Tata Kelola Perusahaan yang Melakukan Penawaran Umum Perdana Saham Disertai Waran (Unit-IPO Firms) - Suherman, Suherman; Ahmad, Gatot (Jurnal Manajemen dan Kewirausahaan, 2017)
The purpose of this research is to determine the difference of corporate governance between unit-IPO firms dan share-only IPO firms. Corporate governance is measured with number of directors, number of outsider directors and debt. Sample of this research covers 40 unit-IPO firms listed in Indonesia Stock Exchange between 2007 and 2014. The results show that there is no difference of corporate governance between unit-IPO firms dan share-only IPO firms.Â https://doi.org/10.26905/jmdk.v5i1.1363